Partisipasi Masyarakat Muslim Dalam Program Bank Sampah Mawar Berbasis Green Economy di Desa Marengan Daya - Alifia Rahma; Dahruji Dahruji; Mashudi Mashudi (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Waste management is something that needs to be done to keep the environment clean. To raise awareness in processing waste, incentives are needed that are directly beneficial to the community. The presence of a Green Economy-based waste bank is the answer to problems that occur in the waste management process. The Mawar Waste Bank, which was established in Marengan Daya Village, is a community that was established to convert waste into goods that have economic value so that through waste management it can become a new source of income for the people of Marengan Daya Village. The purpose of this research is to find out what factors influence the participation of the Muslim community in Marengan Daya Village in the Green Economy-based Mawar Waste Bank program. The type of research approach used is a quantitative approach with the research subjects being members of the Mawar Waste Bank. The results of this research are the discovery of new factors that influence the participation of the Muslim community in Marengan Daya Village in the Green Economy-based Mawar Waste Bank program.